Evaluation of Stiffness and Stress of External Fixators with Curved Acrylic Connecting Bars - Shahar, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The use of acrylic connecting bars in external fixators has become widespread in veterinary orthopaedics. One of the main advantages of an acrylic connecting bar is the ability to contour it into a curved shape. This allows the surgeon to place the transcortical pins according to safety and convenience considerations, without being bound by the requirement of the standard stainless steel connecting bar, that all transcortical pins be in the same plane.The purpose of this study was to evaluate the stiffness of unilateral and bilateral medium-sized external fixator frames with different curvatures of acrylic connecting bars. Finite element analysis was used to model the various frames and obtain their stiffness under four types of load: Axial compression, four-point medio-lateral bending, fourpoint antero-posterior bending and torsion. The analysis also provided the maximal pin stresses occurring in each frame for each loading condition.Based on the results of this study, curvatures of acrylic connecting bars of up to a maximal angular difference between pins of 25° will result in very similar stiffness and maximal pin stresses to those of the equivalent, uniplanar stainless steel system. In both unilateral and bilateral systems the stiffness decreases slightly as angulation increases for axial compression and medio-lateral bending, increases slightly for torsion and increases substantially for antero-posterior bending.External fixator systems with curved acrylic connecting bars are commonly used in veterinary orthopaedics. This paper evaluates the biomechanical performance of such systems by applying the finite element analysis method. It shows that external fixators with curved acrylic connecting bars exhibit stiffness and maximal pin stresses which are similar to those of the standard stainless steel system.
Keywords: External fixator; acrylic connecting bar; stiffness; stress; finite element analysis